THE EPIDEMIOLOGY AND CLINICAL FEATURES OF SEPTIC ARTHRITIS CASES SECONDARY TO KINGELLA KINGAE IN COMPARISON TO SEPTIC ARTHRITIS FROM OTHER PATHOGENS. (18th May 2018) - ElBared, Jessica; Vallières, Émilie; Renaud, Christian; Gravel, Jocelyn; Chartrand, Caroline; Rallu, Fabien; Ouyang, YongMu
Abstract: BACKGROUND: In Europe, Kingella kingae (Kk) is considered as a significant pathogen in osteoarticular infections (OAI) in young children. Some authors suggest that a significant portion of 'culture negative septic arthritis' may be secondary to the inability to isolate K. kingae using conventional methods. However, its pathogenic role and prevalence remain controversial in North America. Since 2014, in order to optimize the microbiological diagnosis of OAI, all osteo-articular specimens submitted to our laboratory for bacteriology culture were simultaneously tested with a home brew multiplex PCR assay detecting Kk, Staphylococcus aureus, Streptococcus pyogenes, Streptococcus agalactiae and Streptococcus pneumoniae . Consequently, an important increase in Kk OAI proven cases was observed. The clinical presentation of Kk OAI comparatively to the other most common pathogens seen in paediatric OAI has yet to be described in North America. OBJECTIVES: The aim of this study is to review all cases of acute septic arthritis (SA) in our institution to define the prevalence of Kk SA and to compare the clinical presentation of SA cases according to their bacterial etiology, with a deeper look at SA caused by Kk . DESIGN/METHODS: We conducted a retrospective chart review of all cases of suspected SA who had a synovial fluid sample submitted for bacteriology culture and multiplex PCR analysis to our microbiology laboratory between May 2014 and May 2017. Only cases of acute SA (< 1 month symptom duration prior to diagnosis) were included. Children with final diagnosis that were not of infectious origin (e.g. rheumatoid arthritis, transient synovitis, etc) were excluded. Probable SA cases were defined as cases with a clinical presentation concordant with SA without any causative bacteria identified, that have received antibiotic treatment for >2 weeks. Eligible SA cases were then stratified into 4 groups according to the final microbiology diagnosis: Kk SA, S. aureus SA, "other bacteria" SA or probable SA. One-way ANOVA with Tukey's multiple comparison test if appropriate was subsequently performed to compare demographics, clinical and biochemical data, duration of treatment and outcome between subgroups. RESULTS: Of the 153 patients who submitted a synovial fluid sample, 71 met the inclusion criteria. A microorganism was found in 56 patients (79%): Kk was found in 37 cases (52%), S. aureus in 11 cases (15%), S. pyogenes in 7 patients (10%), and Salmonella in 1 patient (1%); and there were15 probable SA cases (21%). Interestingly, Kk cases were proven by PCR only in 86% (n=32/37) of cases (culture was negative). One-way ANOVA showed a significant difference in age between subgroups [F(3, 67) = 13, 60, p<0, 0001]:patients infected by Kk were younger (M=1, 50 years old, SD=0, 68) than S. aureus (M=7.48, SD=4.84), "other bacteria" (M=5, 86, SD=4, 37) and probable SA subgroups (M=5, 80, SD=4, 90). The duration of fever (days) was shorter [F(3, 67) = 14, 07, p=0, 028] in patients with Kk (M=4, 1, SD=3, 3) and probable SA (M=2, 9 SD=3, 6) in comparison to "other bacteria" cases (M=8, 8, SD=8, 3). Also, maximal CRP values [F(3, 67) = 14, 80, p<0, 0001] were lower in Kk (M=42, 7, SD=38, 1) and probable SA (M=36, 4, SD=34, 6) than in SA caused by other bacteria (M=178, 5, SD=98, 8). Similarly, maximal neutrophil count [F(3, 67) = 6.71, p=0, 0005] was lower in Kk cases (M=5, 6 SD=2, 3) in comparison to those infected by other bacteria (M=11, 6, SD=4, 1). CONCLUSION: In our institution, since the implementation of multiplex PCR testing for OA samples, Kk has become the most prevalent pathogen causing SA. Children with Kk SA appear to be younger and to have a less inflammatory clinical presentation, as shown by a shorter duration of fever, lower CRP and lower neutrophil values in comparison to cases attributable to other bacteria. Prevalence of Kk SA is probably underestimated in settings where only bacteriology culture is performed.